2019
DOI: 10.1186/s13011-019-0215-4
|View full text |Cite
|
Sign up to set email alerts
|

Age related medication for addiction treatment (MAT) use for opioid use disorder among Medicaid-insured patients in New York

Abstract: Background Medication for addiction treatment (MAT) has received much attention in recent years for treating individuals with opioid use disorders (OUD). However, these medications have been significantly underused among particular subgroups. In this paper, we describe the age distribution of treatment episodes for substance use disorder among Medicaid beneficiaries in New York and corresponding MAT use. Methods Using New York Medicaid claims, we identified individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…(9,21,23) While OUD can impact any individual regardless of age, the pediatric and adolescent stages represent important periods for intervention as most individuals report use before 25 years of age. (9,24,25) This nding is similarly re ected in our data, where patients who had an ED visit for opioid overdose in the last year started using opioids at a mean age of 22.4 years. Recent literature has highlighted that a large proportion of individuals in treatment for OUD are actually young adults but only a small number of them are receiving MAT.…”
Section: Sociodemographic Characteristicssupporting
confidence: 80%
See 1 more Smart Citation
“…(9,21,23) While OUD can impact any individual regardless of age, the pediatric and adolescent stages represent important periods for intervention as most individuals report use before 25 years of age. (9,24,25) This nding is similarly re ected in our data, where patients who had an ED visit for opioid overdose in the last year started using opioids at a mean age of 22.4 years. Recent literature has highlighted that a large proportion of individuals in treatment for OUD are actually young adults but only a small number of them are receiving MAT.…”
Section: Sociodemographic Characteristicssupporting
confidence: 80%
“…Recent literature has highlighted that a large proportion of individuals in treatment for OUD are actually young adults but only a small number of them are receiving MAT. (24)(25)(26) This underuse of an effective treatment in a vulnerable population is certainly alarming. (27) For these reasons, further research is needed on identifying barriers to accessing treatment both within and outside the clinical environment for younger adults with OUD.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…This finding is in keeping with current research that younger individuals are often at higher risk of both fatal and non-fatal overdoses, highlighting the need for further advocacy and research to improve outcomes for this population [ 9 , 21 , 23 ]. While OUD can impact any individual regardless of age, the pediatric and adolescent stages represent important periods for intervention as most individuals report use before 25 years of age [ 9 , 24 , 25 ]. This finding is similarly reflected in our data, where patients who had an ED visit for opioid overdose in the last year started using opioids at a mean age of 22.4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, driving short distances for the treatment can decrease the rate of opioid-related mortality [6]. Despite the demonstrated effectiveness of the FDA-approved medications for the treatment of opioid-use disorder (OUD), studies have demonstrated low rates of treatment use [7]. In 2017, over 70 percent of people who needed treatment for OUD did not receive medication [8].…”
Section: Introductionmentioning
confidence: 99%